Uso de los materiales extraídos en el proceso de excavación del “túnel San eduardo" - Bacuy Ortiz, Osvaldo David (2011)
The municipal authorities aware of the traffic problem experienced by the city of Guayaquil, has directed its actions to implement a series of projects that would help the vehicular flow. To reduce the travel time required by vehicles coming from the south and try to use the way for Duale, which currently has 10 service lanes, the City has planned the construction of a tunnel crossing the hill of Paradise, permitting join this southern city with the north in a few minutes. In recent years, these problems increase due to the labor force that resides in the southwest of Guayaquil and works in the industrial north of the city as well as smaller producers of other counties that enter the city by a Daule after suffering the serious delays caused by traffic in this sector and used to date the distributor of Km 4.5 and then perform one of the tours. To resolve this problem of road network in the city, the Most Illustrious Municipality of Guayaquil, which raises an important proposal is to incorporate a new road link connecting the heat exchanger Km 4.5 of the way for Duale and distributes motor traffic of floods and Firefighter Carlos Julio Arosemena, to connect with Barcelona Avenue, in a less than five minutes, and from this point go to the west and finally south-west suburb of the city.